Portrait de l’artiste en boule de feu - Geneviève Brisac (Sillages Critiques)
Not a paper in the academic sense, a series of organized reflections, a writer expressing her thoughts and feeling when facing the work of another woman writer. An intuition. The outcropping of secret llnks and correspondances.